Gender Differences in Online Behavior: Exploring the Moderating Effect on Loneliness and Cyberslacking among University Students - Rinaldi, Martaria Rizky; Aini, Luthfi Noor; Kurniawan, Aditya Putra (Psympathic : Jurnal Ilmiah Psikologi, 2024)
Academic demands are capable of creating pressure, prompting students to find diversion through smartphone use and internet browsing. Unproductive internet use during learning is termed cyberslacking, a behavior known to be associated with loneliness. Therefore, this research aimed to explore the moderating role of gender in the relationship between loneliness and cyberslacking among university students. Using a quantitative correlational method, the investigation collected demographic data and adopted two scales, including the UCLA-3 Loneliness Scale and Cyberslacking Scale. Participants, comprising 226 students aged 18 to 25 years, were subjected to both descriptive and moderation analysis using Jamovi. The results showed that there was a significant influence of loneliness on cyberslacking, with gender identified as a moderator in such relationship. Recognizing gender differences in online behavior was crucial for enhancing the effectiveness of university policies and intervention strategies.